Under-expression of the Auxin Response Factor Sl-ARF4 improves post-harvest behavior of tomato fruits - Sagar, Maha (Landes Bioscience, 2013)
Auxin is one of the most prominent phytohormones regulating many aspects of fleshy fruit development including fruit set, fruit size through the control of cell division and cell expansion, and fruit ripening. To shed light on the role of auxin fruit ripening, we have previously shown that Sl-ARF4 is a major player in mediating the auxin control of sugar metabolism in tomato fruit (cv MicroTom). Further extending this study, we show here that down-regulation of Sl-ARF4 in tomato alters some ripening-related fruit quality traits including enhanced fruit density at mature stage, increased firmness, prolonged shelf-life and reduced water (weight) loss at red ripe stage. These findings suggest that Sl-ARF4 plays a role in determining fruit cell wall architecture and thus providing a potential genetic marker for improving post-harvest handling and shelf life of tomato fruits.